2017
DOI: 10.1002/hbm.23888
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity changes following interpersonal reactivity

Abstract: Attachment experiences substantially influence emotional and cognitive development. Narratives comprising attachment-dependent content were proposed to modulate activation of cognitive-emotional schemata in listeners. We studied the effects after listening to prototypical attachment narratives on wellbeing and countertransference-reactions in 149 healthy participants. Neural correlates of these cognitive-emotional schema activations were investigated in a 7 Tesla rest-task-rest fMRI-study (23 healthy males) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…The statistical threshold was Bonferroni corrected for the number of rmANOVAs ( p < .017, representing p < .05). These results were previously published within a validation process of the shortened narratives (Krause et al , 2017).…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…The statistical threshold was Bonferroni corrected for the number of rmANOVAs ( p < .017, representing p < .05). These results were previously published within a validation process of the shortened narratives (Krause et al , 2017).…”
Section: Methodssupporting
confidence: 66%
“…Listening to a narrative characteristic of insecure‐preoccupied discourse led to the highest impairment of the listeners’ well‐being, while listeners’ evaluation of friendliness and tendency for friendly social interaction towards the narrator was lowest following the insecure‐dismissing narrative (Kirchmann et al , 2011). These results could be replicated (Krause et al , 2017). In a similar paradigm, there was no systematic difference in response between clinically inexperienced listeners (students) and trained therapists to these prototypical attachment narratives (Martin et al , 2007).…”
Section: Psychopathologymentioning
confidence: 77%
See 1 more Smart Citation
“…Departing from this background, if attachment influences the development of the self, the constitution, and the differentiation of the self and others and is considered closely linked to SR processing (Brockman, 2002 ; Northoff, 2011 ), we may expect an impact on the spontaneous/resting state activity of the brain, as suggested by a study showing a relation between increased measures of individual negative childhood experiences and a more entropic neuronal activity in medial prefrontal cortex during rest (Duncan et al, 2015 ; see Figure 1 ). Moreover, research on the resting state fMRI showed that emotional processing of attachment-related content induces carryover effects and alters the brain network configurations at rest (Krause et al, 2016 , 2018 ; Borchardt et al, 2018 ).…”
Section: Early Relational Experiences Attachment and The Developmentmentioning
confidence: 99%
“…Similar to the above stimulation techniques, functional connectivity changes can also be provoked by mood induction paradigms, where data acquisition is carried out right after specific stimulation (Figueroa et al, 2017; Krause et al, 2018). These applications are likely to yield important clinical information since they are between resting-state and task-specific connectivity.…”
Section: Functional Connectivitymentioning
confidence: 99%